2010
DOI: 10.1115/1.4002785
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of Piezoelectric Energy Harvesting From Aeroelastic Vibrations Using the Doublet-Lattice Method

Abstract: Multifunctional structures are pointed out as an important technology for the design of aircraft with volume, mass, and energy source limitations such as unmanned air vehicles (UAVs) and micro air vehicles (MAVs). In addition to its primary function of bearing aerodynamic loads, the wing/spar structure of an UAV or a MAV with embedded piezoceramics can provide an extra electrical energy source based on the concept of vibration energy harvesting to power small and wireless electronic components. Aeroelastic vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
72
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 30 publications
2
72
0
1
Order By: Relevance
“…In addition, [18] developed a three degree of freedoms model for an airfoil actioned by control surfaces. These models [14,15,16,17,18] were able to predict the voltage and power responses at the flutter speed with the combination of unsteady aerodynamic loads. The airfoil model [14] was also validated against the wind tunnel test results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, [18] developed a three degree of freedoms model for an airfoil actioned by control surfaces. These models [14,15,16,17,18] were able to predict the voltage and power responses at the flutter speed with the combination of unsteady aerodynamic loads. The airfoil model [14] was also validated against the wind tunnel test results.…”
Section: Introductionmentioning
confidence: 99%
“…flutter instability case, were developed. In addition to the time domain model with unsteady aerodynamic calculation via Vortex Lattice Method proposed by [15], a frequency domain model with unsteady aerodynamic calculation via Doublet Lattice Method has been formulated by [16]. A coupled model considering the electromagnetic field is proposed by [17].…”
Section: Introductionmentioning
confidence: 99%
“…Elvin et al 10 have presented a theoretical model for a piezoelectric cantilever pipe that shows that the greatest effect upon flutter speed is produced by the location of the piezoelectric layer, while variation in the piezoelectric capacitance has a relatively small effect. Marqui et al 11,12 have found that, compared with continuous electrodes, segmented electrodes can improve the performance of piezo-aeroelastic energy harvesters by avoiding the cancellation of electrical outputs from the torsional component of the coupled bending-torsion motions of flutter. They also performed numerical investigations on the combined piezoelectric and electromagnetic mechanisms needed to harvest energy from the flutter motion.…”
Section: Introductionmentioning
confidence: 99%
“…Erturk et al [3] performed an experimental study on generating electricity from thin curved airfoils with macro-fiber composite (MFC) piezoceramics under airflow excitation. De Marqui et al [4] studied the piezoaeroelastic problem of energy harvesting with respect to the airflow excitation of a cantilevered plate with embedded piezoceramics. Tang et al [5] proposed a flexible energy harvester inspired by flapping flag dynamics.…”
Section: Introductionmentioning
confidence: 99%